Monitoring the censored lognormal reliability data in a three-stage process using AFT model - Azam Goodarzi; Amirhossein Amiri; Shervin Asadzadeh (Journal of Industrial Engineering International, 2016)
Improving the product reliability is the main concern in both manufacturing and service processes which is obtained by monitoring the reliability-related quality characteristics. Nowadays, products or services are the result of processes with dependent stages referred to as multistage processes. In these processes, the quality characteristic in each stage is affected by the quality characteristic in the previous stages known as cascade property. Two regression-adjusted control schemes are applied to monitor the output quality variables of interest. Moreover, censoring is among the main limitations while monitoring the reliability-related quality characteristics, causing not to record the real values of some observations. Hence, the right censored observations are used to extend monitoring schemes under both the fixed- and variable-competing risks. In this paper, the accelerated failure time (AFT) is used to relate the reliability-related quality characteristic with lognormal distribution to the incoming variables. Then, two cause-selecting control charts are developed to monitor outgoing quality variables when censoring happens in each reliability-related stage. The performance of the control charts is evaluated and compared through extensive simulation studies under the censored and noncensored scenarios.
Keywords: 650; Accelerated failure time (AFT) model; Multistage process; Cascade property; Regressionadjusted control schemes; Fixed- and variable-competing risks